Blood vessel assessment using computed tomography : Effects of ephedrine on uterine artery - Yin, Yibo; Liu, Can; Gao, Guangjian; Li, Jingjing; Long, Xuechen; Zhang, Peijin; Guo, Wenjun (Frontiers in Pharmacology, 2022)
Background: Ephedrine increased blood pressure due to the contractile properties of resistance vessels. Excessive contraction of the uterine arteries might cause fetal distress. This study was to determine the diameter of the uterine artery of female New Zealand rabbits after the administration of different doses of ephedrine using CT. Methods: Thirty-two rabbits were randomly divided into a control group (Group C), low dosage group (Group L), medium dosage group (Group M) and high dosage group (Group H). Normal saline and doses corresponding to the human dose of 7.5 mg, 15 mg and 30 mg of ephedrine were injected respectively. The marginal ear and uterine artery diameters were measured 5, 10, 15, 30, and 45 min after injection using CT, and the hemodynamic changes were recorded. Results: The increase in mean arterial pressure in group M (p =0.009), and H (p =0.013) was higher than that in group C. Compared with group C, substantial contraction of the marginal ear artery was observed at the three doses of ephedrine. There were no differences in the uterine artery diameter among groups L, M and C, However, in Group H, a significant contraction of the uterine artery compared with the other groups (p <0.001) was observed. Discussion: CT can be used to evaluate the effects of drugs on organs and blood vessels. Ephedrine can not only constrict the peripheral blood vessels but also do not affect the uterine artery at a dose of 15 mg or less. However, the dose should not exceed 30 mg, which may cause severe uterine artery depression.